Analisis Visualisasi Tokoh Ajo Kawir Pada Film Seperti Dendam, Rindu Harus Dibayar Tuntas Karya Edwin Dan Eka Kurniawan - Rifa Shandhika; Jupriani Jupriani (Universitas Katolik Widya Karya Malang, 2023)
There are two objectives of this research. First, analyzing the visualization of the character Ajo Kawir in the film Like Revenge, Longing Must Also Be Paid Fully. Second, to analyzing the meaning visualization of Ajo Kawir's character in the film Like Revenge, Longing Must Also Be Paid Completely. This type of research is descriptive qualitative with visual analysis method to explore various visual aspects that describe Ajo Kawir's character, including his physical appearance, facial expressions, gestures, and interactions with the environment and other characters. Data collection techniques using observation and documentation. The data analysis technique of this research is to use studies, namely Charles Sanders Pierce's Semiotics through icons, symbols, and indexes that focus on Ajo Kawir's impotence. The object of this research is the film